2017
DOI: 10.4314/sajas.v47i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary physical form and dietary inclusion of probiotic and enzyme on growth performance, cellular and humoral immunity, and relative weights of lymphoid organs at early period of broiler chickens fed triticale-based diets

Abstract: The aim of the present study was to investigate interactions between feed form and dietary inclusion of probiotics (live organisms) and enzymes on growth performance, cellular and humoral immunity, and relative weights of lymphoid organs of broiler chicks fed a triticale-based diet. A total of 640 broiler chicks were allocated to eight treatments when they were one day old, with four replicates (n = 20 chicks in each). The dietary treatments consisted of feed form (pellets or mash) and dietary supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This suggests that probiotics could play a crucial role in improving growth rates even in challenging dietary situations. A study observed, significant improvement in Feed conversion ratio (FCR), Feed intake (FI) and on weight gain (WG) in broiler hens fed with triticalate-based diet enriched with probiotics and enzymes [22]. The ileal digestibility coefficient of proteins, starch, and gross energy all improved significantly (P ≤ 0.05) when the probiotic (Bacillus subtilis) was added to the broiler diets of both nutrient-adequate and nutrient-deficient birds [23].…”
Section: Effect On Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that probiotics could play a crucial role in improving growth rates even in challenging dietary situations. A study observed, significant improvement in Feed conversion ratio (FCR), Feed intake (FI) and on weight gain (WG) in broiler hens fed with triticalate-based diet enriched with probiotics and enzymes [22]. The ileal digestibility coefficient of proteins, starch, and gross energy all improved significantly (P ≤ 0.05) when the probiotic (Bacillus subtilis) was added to the broiler diets of both nutrient-adequate and nutrient-deficient birds [23].…”
Section: Effect On Growth Performancementioning
confidence: 99%
“…Improvement in feed intake, feed conversion ratio and body weight [18] Bacillus based triticale diet Increased feed intake, feed conversion ratio and weight gain along with cellular immunity [22] B. subtilis Improvement in intestinal digestibility coefficients for starch, crude protein, and overall gross energy…”
Section: Bacillus Subtilismentioning
confidence: 99%